What Drives Innovative Work Behavior? Exploring the Roles of Business Acumen, Person-Job Fit, and Intrinsic Work Motivation - Iqbal, Rofiq; Etikariena, Arum (Psikostudia : Jurnal Psikologi, 2025)
PT RF, as one of the companies in Indonesia, faces challenges in the era of globalization and increasingly intense business competition. Innovative work behavior has become one of the critical factors determining the sustainability and competitive advantage of the organization. The phenomenon of dynamic changes in the business environment, technological advancements, and evolving consumer demands require organizations to continuously innovate in creating better products, services, or processes. This study aimed to identify factors influencing innovative work behavior by testing whether business acumen, person job fit, and intrinsic motivation could be predictors. Hypothesis testing used multiple regression analysis involving 239 employees at PT RF. The hypothesis testing involved multiple regression analysis and utilized a convenience sampling technique. The research data was collected using a questionnaire that was distributed online. The results prove that business acumen acumen (β = .038, t = 10.318, p = < .05) and person job fit (β = .146, t = 2.280, p = < .05) could predict innovative work behavior, meanwhile intrinsic work motivation (β = .044, t = .705, p = > .05) was not able to be a predictor. These findings provide implications for PT RF to give stimulus to improve employees' business acumen and perception of person job fit, encouraging them to behave innovatively. PT RF sebagai salah satu perusahaan di Indonesia mengadapi tantangan pada era globalisasi dan persaingan bisnis yang semakin ketat. Perilaku kerja inovatif menjadi salah satu faktor kritis yang menentukan keberlangsungan dan keunggulan kompetitif organisasi. Fenomena perubahan lingkungan bisnis yang dinamis, kemajuan teknologi, dan tuntutan konsumen yang terus berkembang menuntut organisasi untuk terus berinovasi dalam menciptakan produk, layanan, atau proses yang lebih baik. Untuk itu, penelitian ini bertujuan mengidentifikasi faktor-faktor yang memengaruhi perilaku kerja inovatif dengan menguji apakah business acumen, person job fit, dan motivasi kerja intrinsik mampu berperan sebagai prediktor. Pengujian hipotesis menggunakan analisis multiple regression dengan melibatkan 239 pegawai di PT RF dari berbagai jenjang jabatan. Partisipan diperoleh dengan teknik pengambilan sampel menggunakan convenience sampling dan data dihimpun melalui kuesioner yang disebarkan secara daring. Hasil penelitian membuktikkan bahwa business acumen (β = .038, t = 10.318, p = < .05) dan person job fit (β = .146, t = 2.280, p = < .05) dapat memprediksi perilaku kerja inovatif. Sementara itu, motivasi kerja intrinsik (β = .044, t = .705, p = > .05) tidak mampu menjadi prediktor. Temuan ini memberikan implikasi bagi PT RF untuk memberikan stimulus dalam meningkatkan business acumen serta persepsi person job fit pegawai agar mereka terdorong untuk berperilaku inovatif.